Pressure and magnetic field effects on ferroelastic and antiferromagnetic orderings in honeycomb-lattice Mn2V2O7 - Wu, H. C.; Hsieh, D. J.; Yen, T. W.; Sun, P. J.; Kakarla, D. Chandrasekhar; Her, J. L.; Matsuda, Y. H.; Chang, C. K.; Lai, Y. C.; Gooch, M.; Deng, L. Z.; Webber, Kyle Grant; et al. (Physical Review B, 2020)
The multiferroic nature of the honeycomb-lattice Mn2V2O7 was investigated through detailed temperature, high-pressure, and magnetic-field-dependent measurements. A first-order martensiticlike structural phase transition with the thermal hysteresis associated with magnetic, heat-capacity, and dielectric anomalies was observed between T-Mh (303 K) and T-Mc (291 K). External pressure up to 15.41 kbar suppresses the thermal hysteresis in the magnetization data, indicating that the high-temperature beta-phase persists down to the lower temperature under 15.41 kbar. Furthermore, isothermal capacitance-stress hysteresis loops along with crystallographic Aizu notation of 2/mF (1) over bar supports a martensitic phase transition driving ferroelastic ordering near or below room temperature. At low temperature, a long-range antiferromagnetic ordering was observed at T-N similar to 17 K. With increasing the external pressure up to 15.41 kbar, 100% enhancement of T-N was observed and a metamagnetic transition at 5 K was enhanced near 3 T. High-field magnetization study up to 60 T induces multiple metamagnetic transitions below T-N. Below T-N, a magnetostriction induced magnetoelectric coupling was observed and further supported by the temperature-dependent x-ray studies. Taking these comprehensive research findings into account, we established that Mn2V2O7 is a unique multifunctional material with the coexistence of ferroelastic and antiferromagnetic orderings and with weak magnetoelectric coupling.
CRIS-Team WoS Importer:2020-09-04